Improved performance of protein‐based recombinant gene therapy vehicles by tuning downstream procedures. (16th September 2013) - Unzueta, Ugutz; Saccardo, Paolo; Ferrer‐Miralles, Neus; García‐Fruitós, Elena; Vazquez, Esther; Villaverde, Antonio; Cortés, Francisco; Mangues, Ramón
<x xml:space="preserve">Abstract</x> Protein engineering offers a robust platform for the design and production in cell factories of a plethora of protein‐based drugs, including nonviral gene therapy vehicles. We have determined here that a protein nanoparticle, formed by highly cationic protein monomers, fails to bind exogenous DNA and to promote detectable gene expression in target cells despite recruiting all the needed functions. Removal of DNA and RNA with nucleases previous to forming complexes with exogenous DNA dramatically enhances the ability of the protein to bind and transfer DNA to target cell nuclei. These data point out contaminant nucleic acids deriving from the cell factory as a major factor impairing the performance of protein‐based artificial viruses and stress the need of a nuclease step in the downstream of proteins whose function is based on cationic domains. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29:1458–1463, 2013